2014
DOI: 10.1002/app.41458
|View full text |Cite
|
Sign up to set email alerts
|

A facile dip‐coating approach to prepare SiO2/fluoropolymer coating for superhydrophobic and superoleophobic fabrics with self‐cleaning property

Abstract: In this study, a facile, two‐step dip‐coating approach was reported for the fabrication of the superhydrophobic and superoleophobic cotton fabrics. It was confirmed that the superhydrophobic and superoleophobic composite thin film containing modified‐SiO2 nanoparticles and fluoropolymer had been successfully fabricated on the cotton fabrics surface, the results demonstrated that the treated cotton fabrics showed good performances, such as superhydrophobicity and superoleophobicity, low water and oil absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…The wettability of material is basically decided by its surface energy and the roughness of its surface [24]. Modifying the surface roughness of textiles is normally achieved by loading inorganic particles through various methods [25]. Raw cotton has a relatively rough surface compared to its fabrics.…”
Section: Wettabilitymentioning
confidence: 99%
“…The wettability of material is basically decided by its surface energy and the roughness of its surface [24]. Modifying the surface roughness of textiles is normally achieved by loading inorganic particles through various methods [25]. Raw cotton has a relatively rough surface compared to its fabrics.…”
Section: Wettabilitymentioning
confidence: 99%
“…After the coating of rubber membrane combined with the fluoropolymers (sample F, G and H), the peaks for the functional groups of fluoropolymers (CF 2 and CF 3 ) have slightly shifted due to the formation of tri-fluoroacetic anhydride (-Si-CH 2 -CF 3 ) as a result of their polymerzation reactions with cyclic organosilanes. Fluoropolymers have been involved to make the hydrophobic surface on cotton fabrics as shown in these FTIR spectra [16,20,21]. The CF 2 and CF 3 were deformed and mixed with other rocking bands at 1338 to 1330 cm −1 .…”
Section: Ftir Spectramentioning
confidence: 99%
“…The resulting coated fabric efficiently separated oil from oil-water mixture owing to its superhydrophobicity and superoleophilicity. Lin et al reported superhydrophobic and superoleophobic cotton fabric, which was coated by SiO2 nanoparticles with fluoropolymer (Perfluoroalkyl ethyl acrylate) [20]. In addition, Zhou et al reported a fabrication of superhydrophobic and superoleophobic cotton fabric using chemical vapour deposition method by incorporation of polyaniline with FeCl3·6H2O and 1H,1H,2H,2H-perfluorooctyltriethoxysilane [21].…”
Section: Introductionmentioning
confidence: 98%